2019
DOI: 10.3389/fpsyg.2019.00939
|View full text |Cite
|
Sign up to set email alerts
|

Great Expectations? Relation of Previous Experiences With Social Robots in Real Life or in the Media and Expectancies Based on Qualitative and Quantitative Assessment

Abstract: Social robots, which mostly look and behave like humans, are often perceived as somehow alive and treated similar to humans, despite the fact that they are non-living electronic devices. Based on considerations of the uncertainty reduction theory, the question arises what expectancies regarding social robots people have and what sources they use to achieve these expectancies. To receive an in-depth understanding of people’s expectancies regarding social robots and particularly how these expectancies are influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(61 citation statements)
references
References 49 publications
4
57
0
Order By: Relevance
“…However, it is expected that decisive behavior and some degree of variability (hesitant behavior) might have been perceived as more human-like than the robot that displayed consistently hesitant actions. Literature has shown that people expect robots to be precise, efficient, competent, and reliable with some degree of social skills [23]. This was also revealed on the scales we applied before the experiment.…”
Section: Discussionsupporting
confidence: 56%
“…However, it is expected that decisive behavior and some degree of variability (hesitant behavior) might have been perceived as more human-like than the robot that displayed consistently hesitant actions. Literature has shown that people expect robots to be precise, efficient, competent, and reliable with some degree of social skills [23]. This was also revealed on the scales we applied before the experiment.…”
Section: Discussionsupporting
confidence: 56%
“…Although, we are far from achieving all what the media promises, such exposure to technology has created in the future users high expectations regarding what are the robots capable of. Researchers have focused on developing tools that measure general preferences and expectations toward robots and assessed how those might have an impact on actual human robot interaction as presented by [19]. People would prefer robots that look like machines, with human-like speech and that are predictable, smart but controllable, and polite (for review see [20,21]).…”
Section: Expectations About Robot Behaviormentioning
confidence: 99%
“…From its earliest iterations, Nass and colleagues argued that some individual differences could be important when testing CASA, including demographics (e.g., level of education) and knowledge of technology (Nass & Steuer, 1993). Related findings suggest that CASA effects are moderated by factors such as previous computer experience (Johnson & Gardner, 2007) and that a person's expectations of media agents (e.g., social robots) vary based on their experience (Horstmann & Krämer, 2019). Experience is relevant to CASA's assumption of mindlessness given that experience might determine whether a mindless or mindful response is triggered when encountering a media agent.…”
Section: People Have Changed: Knowledge and Experiences With Media Agmentioning
confidence: 99%